Tinta Alumni from Kuala Pilah to South Korea / Hamizan Azmi - Azmi, Hamizan (UiTM Cawangan Negeri Sembilan, 2022)
I would first like to give my thanks to the editors of this magazine for allowing me to share my past experiences as a student at UiTM Kuala Pilah. I hope that this article can help ease the worries of the new students who are finally seeing the campus for the first time after the Covid-19 pandemic. My name is Hamizan Azmi, or more colloquially known as Mika by several lecturers and friends, and I studied at UiTM Kuala Pilah for my BSc (Hons.) in Biology (2017-2020). For me, Kuala Pilah was definitely not the first campus I had in mind when I got the offer for my degree, however I did not regret it one bit. It is true that UiTM Kuala Pilah is a smaller campus compared to others such as UiTM Shah Alam, but it because of the small campus, environment and friends I have made along the way that allows me to call UiTM Kuala Pilah a home away from home. Since the numbers in my batch are small, we managed to bond with each other well. We created memories with each other from the very first day until the day we went on our own successful different paths.